2016
DOI: 10.1038/srep33952
|View full text |Cite
|
Sign up to set email alerts
|

Thickness of Actinic Keratosis Does Not Predict Dysplasia Severity or P53 Expression

Abstract: The severity of dysplasia and expression of p53 in actinic keratosis (AK) is of importance for the transformation to squamous cell carcinoma. It is assumed that it is most important to treat thick AKs as they are believed to be more dysplastic than thin AKs. However, a relation between AK thickness and dysplasia or the expression of p53 has never been demonstrated. The aim of this study was to investigate this possible relation. Sixty-six AKs were included for clinical and histological examination. Prior to pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
1
12

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 26 publications
2
41
1
12
Order By: Relevance
“…Additionally, another study claims that the severity of AK dysplasia and expression of p53 are independent of clinical and histological thickness . These results challenge the biological significance of the AK I‐III grading system …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, another study claims that the severity of AK dysplasia and expression of p53 are independent of clinical and histological thickness . These results challenge the biological significance of the AK I‐III grading system …”
Section: Introductionmentioning
confidence: 99%
“…They are diagnosed clinically and commonly classified based on the overall thickness of individual lesions . However, recent studies have shown that the thickness of AK lesions neither correlates with its histological grading nor predicts its dysplastic severity . To overcome the limitation of single lesion evaluation, a new clinical classification, called the ‘actinic keratosis area and severity index’ (AKASI), has recently been proposed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a recent study has shown that it is not possible to draw a correlation from clinical appearance to histology [7]. Furthermore, another study revealed that the thickness of AKs does not predict its dysplastic severity and thus its aggressiveness [6]. Therefore, an assessment tool taking the whole field as well as hyperkeratotic lesions into account was required.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies show that the thickness of AK does not predict its degree of dysplasia or correlate with established histological grading systems [6, 7]. Furthermore, a lesion-based classification scheme does not adequately represent the whole area affected by AK.…”
Section: Introductionmentioning
confidence: 99%